Formação continuada de professores na produção acadêmica dos Endipes e as práticas de formação na escola: contextos em diálogos - Costa, Liliane da Silva (2019)
First of all it analyzes the trends, fundamentals and propositions of school-centered continuing education, articulating dialogues between academic production of the National Meetings of Didactics and Teaching Practices (NMDTP), the policy of continuing education of the municipal Education system of Serra city and the practices of continuing education translated into the school. Furthermore it consists of an exploratory research, contemplating: a) bibliographic research on the debate of continuing education centered on the school in the work of NMDTP from 2012 until 2016; b) field research developed with the professionals of a Elementary School I and with the manager of the Training Center of the Municipal Department of Education of Serra city, assuming documentary analysis and comprehensive interview as methodological procedures. Moreover it accepts the assumptions of the authors António Nóvoa and Marie-Christine Josso, with a critical-reflective vision of continuing education and the fundamentals of Carpentier and Lessard (2016); Ball, Maguire and Braun (2016) in the reflection on the continuing education policies of teachers and their translation into the school. Indeed it noted in the academic production of the NMDTP, an expressive discourse of appreciation of the school is observed as a privileged locus of continuing education, in which the formative practices primand by the collectivity and authorship of the teacher and consider the demands of the pedagogical practice. Even more, the field data showed that, although the policy of continuous training of the municipal education system of Serra city is based on an articulated work of diversified training modalities, continued education focused on the school was not assumed as a premise of this policy, considering the few formative moments in the professional’s work day and their timid involvement in this process. To sum up that continued training practices focused on the school need to be configured as a professional culture that recognizes the teacher’s role and the collaborative work among their peers. Finally this involves guaranteeing their right to continuing education in the context of work by enabling educational policies produced by dialogue between school professionals, the representatives of the Department of Education and state and federal institution.